Age related immune modulation of experimental autoimmune encephalomyelitis in PINK1 knockout mice - Cossu, Davide; Yokoyama, Kazumasa; Sato, Shigeto; Noda, Sachiko; Sakanishi, Tamami; Sechi, Leonardo Antonio; Hattori, Nobutaka (Frontiers in Immunology, 2022)
Objective: Recent research has shown that Parkin, an E3 ubiquitin ligase, modulates peripheral immune cells-mediated immunity during experimental autoimmune encephalomyelitis (EAE). Because the PTEN-induced putative kinase 1 (PINK1) protein acts upstream of Parkin in a common mitochondrial quality control pathway, we hypothesized that the systemic deletion of PINK1 could also modify the clinical course of EAE, altering the peripheral and central nervous systems’ immune responses. Methods: EAE was induced in female PINK1-/- mice of different age groups by immunization with myelin oligodendrocyte glycoprotein peptide. Results: Compared to young wild-type controls, PINK1-/- mice showed earlier disease onset, albeit with a slightly less severe disease, while adult PINK1-/- mice displayed early onset and more severe acute symptoms than controls, showing persistent disease during the recovery phase. In adult mice, EAE severity was associated with significant increases in frequency of dendritic cells (CD11C+, IAIE+), lymphocytes (CD8+), neutrophils (Ly6G+, CD11b+), and a dysregulated cytokine profile in spleen. Furthermore, a massive macrophage (CD68+) infiltration and microglia (TMEM119+) and astrocyte (GFAP+) activation were detected in the spinal cord of adult PINK1-/- mice. Conclusions: PINK1 plays an age-related role in modulating the peripheral inflammatory response during EAE, potentially contributing to the pathogenesis of neuroinflammatory and other associated conditions.